Pojęcie instrumentu administracyjnoprawnego — zarys tematyki - Krzysztof Horubski (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The article contains a general consideration of the scope of meaning and the conditions for the use of the term “administrative law instrument” in the field of administrative law science and public (administrative) economic law. The findings of this study serve to show the legitimacy and usefulness of using the title conceptual category in analyses of a functional nature, focusing on the goals, effects, values that the given regulations of the legal order are to serve. The concept-tool “administrative-legal instrument” is undoubtedly characterised by a considerable degree of flexibility, which results from the intuitiveness of its operation and from a certain underdetermination of meaning, which can be filled with content depending on the direction of the research. Therefore, it is also useful for carrying out considerations that go beyond a single branch of law or such considerations that aim to outline the boundaries of a branch division of the law in heterogeneous (complex) sets of regulations that are separated due to the subject of regulation (such as e.g. public procurement law). However, the title concept is secondary to the adopted criteria for defining administrative law, or its delimitation of the scope of administrative law within sets of norms referred to as “borderline law.” The article is also aimed to define the relationship of the title concept to the established category of legal forms of administrative action. With regard to this issue, it is pointed out that the research planes implied by the use of one of these conceptual categories are different (functional plane — objectives, effects to be achieved through a given legal solution / construction plane of a given legal form of activity — requirements for the validity of a given type of action, supervision over using it, means of legal protection of the addressee of the action). Attention is also drawn to the fact that there is no basis for relating the concept of an administrative law instrument to the entire catalogue of legal forms of administrative action, as well as to the possibility of giving the concept of an administrative law instrument a meaning that goes beyond such a catalogue (e.g. including also norms directly regulating administrative law). The argumentation of this study also seeks to demonstrate the legitimacy of the functioning of the two conceptual categories indicated in the conceptual apparatus of the science of administrative law and public economic law.